The political management of Covid-19 in Portugal: analytical insights for the international debate - Correia, Tiago (2020)
As the SARS-CoV-2 pandemics reaches the entire planet the political responses to deal with the coronavirus disease Covid-19 have flourished. However, not only has the evidence on decision-making and outcomes – including the side effects – lacked, but also the policy analysis has not been able to overcome an overly descriptive nature that brings too little to the theoretical understanding of the political management of Covid-19. Building on the Portuguese case, this essay aims to contribute to fill in such blanks, notably by contributing to the improvement of political responses and consolidation of the theoretical debate about political decision-making in the context of health crises. The reflection  expands on the need to clarify the goal of the management of contagions (whether the aim is to eradicate, manage, ignore or if there is an inability to manage the transmission chains), on the quality monitoring and limits of international comparisons (different methodologies and the importance of mass screening), and on aspects of leaving with Covid-19 and quest for normality (challenges in the access to vaccination and links with broader social inequalities). The reflection ends by showing how the Portuguese case resonates on some of the key theories of the analysis of public policies cycles.